A Computational Two‐Scale Model for the Simulation of Dual‐Phase Steels under Cyclic Loading. Issue 1 (17th December 2018) - Gandhi, Ashutosh; Balzani, Daniel; Brands, Dominik; Scheunemann, Lisa; Schröder, Jörg
Abstract: Dual‐Phase (DP) steels exhibit excellent macroscopic properties such as high strength, ductility and energy absorption. However, the increase of strength also results in a large springback behavior which should be considered for an optimal production process design. Thus, accurate modeling of springback during forming applications is important. The macroscopic behavior of DP steels is closely tied to the phenomena taking place on the microstructural level. The presence of kinematic hardening and graded properties in ferrite together with complex interactions of the different phases at the microscale have a large influence on the macroscopic springback response. Therefore, a micro‐macro scale bridging approach is proposed wherein statistically similar representative volume elements (SSRVEs) are considered to capture the DP‐steel microstructure, c.f. [1], [2], [5]. This ensures effective modeling of the microstructure while significantly reducing the complexity of the microstructural morphology and thus reducing the computing time. A mixed hardening model, see [8], along with the initial volumetric strain approach, see [3], enables incorporating the kinematic hardening as well as graded properties in the microstructure. Multiscale calculations of cyclic tests show the performance of the model by measuring the Bauschinger factor and the attained stress levels during deformation.